Analysis of Low Realization For Mudharabah Financing at Muamalat Indonesia Bank, Banda Aceh - Arinal Rahmati; Deni Mulyadi; Januddin Januddin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This study aims to determine the causes of low realization of mudharabah financing at Muamalat Indonesia Bank, Banda Aceh Branch. This research is expected to be a framework or model for other Islamic banks that have the same problem. Data for this study are collected through in-depth interviews and documentation studies. This research uses descriptive analysis method and the results of the data obtained are analyzed qualitatively. The results of the study show that the minimum factor of realization of mudharabah financing is caused by the bank's difficulty in obtaining the income statement accurately, transparently and routinely. In addition, mudharabah products are very vulnerable to the occurrence of moral hazard from business actors (mudharib) who tend to maximize profits resulting in reduced returns to the bank as shahibul mall. Then other factors are also influenced by the ineffectiveness of the profit-sharing financing model relating to entrepreneurs and the lack of interest in the scheme of profit sharing in business activities.